Self Esteem and Sociotropy - Autonomy as predictors of Workplace Burnout among Private Sector Employees - Palak Jaggi; Smriti Sethi (International Journal of Behavioral Sciences, 2025)
Workplace burnout is a growing concern in the private sector, where employees face intense performance pressures, leading to stress and reduced productivity. While job-related factors are well-documented contributors, the role of personality traits in burnout remains an area of interest. This study examines the impact of Self-Esteem, Sociotropy, and Autonomy on Workplace Burnout among private sector employees. A sample of 120 employees was analyzed using ANOVA, Pearson correlation, and multiple regression. The findings reveal that burnout levels significantly differ across employee groups (F = 8.210, p .05). However, Autonomy was negatively correlated with burnout (r = -0.349, p = .027) and significantly predicted lower burnout levels (B = -0.129, p = .025). These results suggest that job autonomy portrays a significant part in reducing burnout, while self-esteem as well as sociotropy may not be direct predictors. The study highlights the need for organizations to enhance job autonomy, implement stress management programs, and adopt flexible work policies to mitigate burnout. Future research should explore additional workplace stressors and long-term intervention strategies. These findings underscore the importance of organizational structures that prioritize employee autonomy and mental well-being. Encouraging participative decision-making, providing opportunities for self-directed work, and promoting supportive leadership can foster a healthier work environment. Moreover, regular mental health assessments and resilience training can help employees manage stress more effectively. By integrating these practices, organizations can not only reduce burnout but also enhance overall job satisfaction, engagement, and long-term productivity among private sector employees.
Keywords: Workplace burnout; autonomy; occupational stress; private sector employees; self-esteem; sociotropy